PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS TELEGRAM PADA SEKOLAH DASAR SWASTA LKIA PONTIANAK SELATAN - Theo Nugroho Pratama; Hery Kresnadi; Suparjan Suparjan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
Abstract The purpose of this article was to develop a telegram-based learning media on the beauty of the diversity of my country in the fourth grade of SDS LKIA South Pontianak. This type of research is a development research using the ADDIE model with the steps of analysis, design, development, implementation, evaluation. Quantitative data were obtained from the product results by the validator as well as filling in the practicality data of learning media by teachers and students. Qualitative data were obtained from suggestions and notes by validators, teachers, and students. The research instrument was in the form of interview guidelines and questionnaires. The level of media validity is based on the results of the assessment by design experts, and material experts, while the practicality level of learning media is based on the learning outcomes of students and teachers of class IV SD LKIA South Pontianak. The results of the validation of learning media design experts obtained an average of 4.9 "very valid". The results of the validation of learning media materials obtained an average of 4.6 "very valid". The results of the practicality of learning media by students get an average of 3.40 "very practical". The results of the practicality assessment of learning media by teachers obtained an average of 3.57 "very practical". Keywords: Leraning Media, Telegram